O ensino e aprendizagem de química orgânica: um estudo de caso envolvendo um curso de formação de professores - Musetti, Henrique Cesar (Universidade Federal de São Carlos, 2025)
Chemistry teaching is permeated by the use of symbols, analogies, images, models, and diverse representations. Especially in initial teacher training courses in Chemistry, issues of communication and language need not only to be presented carefully to students, but also to have reflection on their use encouraged, highlighting that the choice of representational methods can have a direct influence on learning. In the teaching of Organic Chemistry, the use of representations and, often, one or more visualization tools is quite common, with the aim of enabling students to develop concepts and make interpretations aligned with current and evolving chemical knowledge. Therefore, this research sought to characterize, especially, the approaches and resources used in Organic Chemistry in a teacher training course, as well as general aspects of teaching and learning in this context, such as the relationships between the subjects. This research was qualitative in nature, employing questionnaires, semi-structured interviews, and observation as data collection instruments. The data obtained were analyzed through discursive textual analysis (DTA) and from a sociocultural perspective, supported by Wertsch's theory of mediated action. Among the main conclusions of this work, one can cite the positive effects achieved in learning with the use of material objects to aid in three-dimensional structural perceptions, suggesting that early and more frequent use in the subject in question can enhance the teaching and learning of its central concepts, often in association with DICT. The results also revealed that encouraging continuing education for teachers, especially those involved in initial teacher training, can help improve familiarity with these resources as well as their use in teaching practice. Furthermore, the research highlighted the importance of a good relationship between teachers and students for motivation and retention in a challenging subject like Organic Chemistry.
The teaching and learning of organic chemistry: a case study involving a teacher training course
Keywords: Ensino de química; Recursos educacionais; Análise textual discursiva; Chemistry teaching; Educational resources; Discursive textual analysis; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 4. Educação de Qualidade